Erziehungswissenschaft aus der Distanz Empirische Studien - Erdmann, Daniel; Vogel, Katharina (Universitätsverlag Göttingen, 2021)
Scientific research in educational science is not a novelty - at the latest since the 1980s, it has become established through the Commission for Scientific Research of the German Society for Educational Science. Even outside this institutionalized place, one encounters a not inconsiderable number of corresponding studies and publications under this keyword, which affect the disciplinary self-image on different levels and thereby not infrequently attest to a (supposed) peculiarity of the university discipline of educational science in comparison to other disciplines. The empirical investigation of the 'reality' of educational science, as (also) tested in this volume, focuses on different 'problem areas' of the measurement of educational science knowledge and its production. Characteristic for all contributions gathered here is an access to the source material by means of methods of distanced observation, through which semantics, discourse (excerpts), receptions, and reference spaces of educational science are examined exemplarily and in a comparatively abstract perspective, thus allowing conclusions to be drawn about one's own history of knowledge and science. In short: What do we know about educational science when we look at it from a distance? Translated with www.DeepL.com/Translator (free version)